Music education and global fiscal questions. Issue 3 (7th December 2016) - Fautley, Martin; Murphy, Regina
Abstract : Music education is a worldwide activity. Gatherings and conferences where music educators from around the globe meet together are always interesting arenas, with as many discussions going on in the various watering holes near the conference venue as take place in the sessions themselves. But what we actually mean by music education often becomes an absorbing topic in its own right, and one we have discussed previously in these editorials ( inter alia Fautley & Murphy, 2015 ). Differences are not just about matters of delivery, however; they also reflect often complicated local contexts and histories. They are at once philosophical, concerned with policy, concerned with curriculum, with progression, with assessment, with delivery, with modality, with jurisdictional requirements, and with regulations. All this makes for an interesting subject base.